PENERAPAN PROBLEM BASED LEARNING DENGAN GALLERY WALK DALAM PENINGKATAN KETERAMPILAN BERPIKIR KRITIS SISWA - Wiwiet Aji Prihatin (Direktorat Guru Pendidikan Menengah dan Pendidikan Khusus, 2022)
This study aims to improve critical thinking skills through a Problem Based Learning model assisted by a Gallery walk on economic growth and development material for students of class XII IPS-1 SMA Negeri 1 Rawalo. This research is a classroom action research that uses two cycles with the research design referring to the Kemmis-Mc.Taggart model. The implementation of each cycle goes through the stages of planning, action/observation, and reflection. Data were taken with test and non-test instruments which were analyzed by quantitative and qualitative descriptive. The results showed that there was an increase in students' skills from cycle I to cycle II in the aspects of providing simple explanations 22.58%, building basic skills 38.71%, managing strategies and tactics 25.81%, providing further explanations 38.71%, and skills conclude 22.58%. This has an impact on increasing student knowledge by 8.87% and student behavior experiencing positive changes from the active aspect 16.13%, confidence 25.81%, cooperation 9.68%, independent 9.68%, and all students have a positive response. positive towards learning. The application of Problem Based Learning with Gallery walk can improve students' critical thinking skills.